Sistem Informasi Meramalkan Penjualan Barang Dengan Metode Double Exponential Smoothing (Studi kasus: PD. Padalarang Jaya) - Annastasya Lieberty; Radiant V. Imbar (Maranatha University Press, 2015)
PD. Padalarang Jaya is a trading company that sells a variety of daily needs. The company develop an desktop application for point of sales and purchases goods to vendor and also Decision Support System for forecasting stock of goods using the